ANALISIS PERSEPSI MAHASISWA TERHADAP PENGARUH GELOMBANG ELEKTROMAGNETIK DAN PERANGKAT KOMPUTER TERHADAP KESEHATAN - arya Ovaliano; kiki Masayu; indryani afdila; Juwita harahap; zaqi al barkah; adelyna Oktavia Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
In today's era of technological sophistication, computer devices have become a daily necessity for students, which unknowingly their use can trigger exposure to electromagnetic waves that have an impact on students' health. This study aims to examine students' perceptions regarding the impact of computer device use and electromagnetic wave exposure that is felt on their health conditions. Based on data from 26 respondents, it shows that the majority of students experience complaints about their physical health conditions, such as headaches (65.4%), fatigue (46.2%), eye pain (46.2%), and neck or back pain (46.2%) with a range of device usage time between 1-5 hours per day. In addition, students often use devices in dark rooms, do not use radiation protection, and 23.1% of respondents rarely rest after using devices which can worsen their health conditions. However, even though these impacts have been realized, most respondents have not been consistent in implementing preventive measures. This study reminds us of the importance of increasing awareness that needs to be formed as a healthy habit for students to be wiser in using computer devices so that they remain beneficial for them without being affected by negative impacts.